Diarrhea in children younger than 5 years old in a family health unit - Juliana Rogéria Pereira; Laíza Strinta; Grasiela Cristina Silva Botelho; Juarez Coimbra Ormonde Junior; Lincoln Christian Barros (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769213490 Objective: To characterize, by means of form A (registration form of families), medical records and reports of the Epidemiological Surveillance System, sociodemographic and environmental aspects in children under five with diarrhea in the Family Health Strategy. Method: This is a quantitative study with document analysis. The population of the study  consisted of 13 children enrolled in a family health strategy. Results: The age group most affected by diarrhea is the one comprising 1 year old to 1 year and 11 months old. There was relative discrepancy between the data from the medical records and the data from the Epidemiological Surveillance System in relation to the treatment plan offered. In addition, there was absence of medical records for some cases reported in the system, which is a severe difficulty that directly affects the quality the profile of the children and the identification of issues related to the registration of information.